Perilaku Konsumtif Mahasiswa dalam Era E-commerce: Perspektif Pengalaman dan Praktik Konsumsi Digital - Abigaiel. C Lesbasa; Hwihanus (Penerbit Jurnal Indonesia, 2026)
The growth of e-commerce in Indonesia has transformed consumer patterns, particularly among students who are active in the digital ecosystem. This study aims to analyze how students interpret and experience consumer behavior in their use of e-commerce, as well as how these consumption practices take shape in their daily lives. The theoretical framework employed includes Social Practice Theory, which views consumption as the result of an interaction between meaning, material, and competence, as well as consumer behavior theory and the concept of impulse buying. This study adopts a qualitative descriptive approach using a case study method among students at the University of 17 August 1945 in Surabaya. Data collection was conducted through in-depth interviews) with informants selected using purposive sampling, followed by analysis using thematic analysis. The findings indicate that students’ consumption behavior is not uniform but rather diverse and influenced by subjective experiences, digital habits, and interactions with e-commerce features such as discounts, flash sales, and social media exposure. Three consumption patterns were identified: impulsive, moderate, and planned, which are determined by each individual’s self-control and financial management capabilities. This study concludes that consumer behavior is a social practice shaped by the interaction between internal and external factors within the digital ecosystem.